2018
DOI: 10.1177/0958305x18802775
|View full text |Cite
|
Sign up to set email alerts
|

Influences of ambient conditions on the performance of proton exchange membrane fuel cell using various models

Abstract: Proton exchange membrane fuel cell is an emerging renewable energy resource for transportation and power generation. Similar to other renewable resources, the performance of proton exchange membrane fuel cell is affected by ambient conditions. However, procedures for analyzing the influences of such conditions on the performance of proton exchange membrane fuel cells are expensive and time-consuming. Moreover, the commonly used models have been developed on the basis of standard ambient conditions. Thus, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…[33][34][35][36][37][38][39][40][41][42][43] These models use passive as well as active electrical components that are combined both in series and in parallel and can accurately emulate the voltage produced by PEMFC systems. [33][34][35][36][37][38][39][40][41][42][43] These models use passive as well as active electrical components that are combined both in series and in parallel and can accurately emulate the voltage produced by PEMFC systems.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[33][34][35][36][37][38][39][40][41][42][43] These models use passive as well as active electrical components that are combined both in series and in parallel and can accurately emulate the voltage produced by PEMFC systems. [33][34][35][36][37][38][39][40][41][42][43] These models use passive as well as active electrical components that are combined both in series and in parallel and can accurately emulate the voltage produced by PEMFC systems.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, previous studies have demonstrated that the ambient conditions profoundly affect the PEMFC performance, 40,[75][76][77][78][79] indicating that it would be meaningful to incorporate ambient variations in the fault diagnosis model. Yet, previous studies have demonstrated that the ambient conditions profoundly affect the PEMFC performance, 40,[75][76][77][78][79] indicating that it would be meaningful to incorporate ambient variations in the fault diagnosis model.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations